2008
DOI: 10.1158/1078-0432.ccr-08-1086
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Tumor-Associated Antigen, Cadherin 3/P-Cadherin, as a Possible Target for Immunotherapy of Pancreatic, Gastric, and Colorectal Cancers

Abstract: Purpose: To establish cancer immunotherapy, it is important to identify the tumor-associated antigens (TAA) that are strongly expressed in the tumor cells but not in the normal cells. In this study, to establish an effective anticancer immunotherapy, we tried to identify the useful TAA of pancreatic cancer. Experimental Design: Based on a previous genome-wide cDNA microarray analysis of pancreatic cancer, we focused on cadherin 3 (CDH3)/P-cadherin as a novel candidateTAA for anticancer immunotherapy. To identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
110
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 42 publications
1
110
0
Order By: Relevance
“…85 P-cadherin has been suggested as a possible target for immunotherapy of pancreatic, gastric, and colorectal cancers based on the identification of HLA-A2-restricted cytotoxic T lymphocyte epitopes of P-cadherin in HLA-A2.1 transgenic mice, and the in vitro and in vivo cytotoxicity against tumor cells of cytotoxic T lymphocyte specific to CDH3 induced from HLA-A2-positive healthy donors and cancer patients. 86 In conclusion, this study shows the value of P-cadherin expression as a marker of poor prognosis in a large breast cancer series. P-cadherin positivity is associated with high-grade tumor subtypes (HER2 þ and basal carcinomas), and well-established markers of poor prognosis (ER, PR, Bcl-2), and may represent a promising antibody therapeutic target, either by exploiting its association with poor prognosis tumor, or by modulating its role in cell adhesion and migration.…”
Section: G Turashvili Et Almentioning
confidence: 59%
“…85 P-cadherin has been suggested as a possible target for immunotherapy of pancreatic, gastric, and colorectal cancers based on the identification of HLA-A2-restricted cytotoxic T lymphocyte epitopes of P-cadherin in HLA-A2.1 transgenic mice, and the in vitro and in vivo cytotoxicity against tumor cells of cytotoxic T lymphocyte specific to CDH3 induced from HLA-A2-positive healthy donors and cancer patients. 86 In conclusion, this study shows the value of P-cadherin expression as a marker of poor prognosis in a large breast cancer series. P-cadherin positivity is associated with high-grade tumor subtypes (HER2 þ and basal carcinomas), and well-established markers of poor prognosis (ER, PR, Bcl-2), and may represent a promising antibody therapeutic target, either by exploiting its association with poor prognosis tumor, or by modulating its role in cell adhesion and migration.…”
Section: G Turashvili Et Almentioning
confidence: 59%
“…Interestingly, in 2008, Imai and collaborators have suggested CDH3/P-cadherin as a possible target for immunotherapy of pancreatic, gastric, and colorectal cancers, since it was identified as a novel tumour-associated antigen, meaning that was strongly expressed in tumour cells, but not in normal cells (Imai et al, 2008). Indeed, we have found that P-cadherin silencing, in breast cancer cells inoculated in nude mice, was able to significantly inhibit in vivo tumour growth (unpublished data).…”
Section: P-cadherin -Potential Therapeutic Target In Cancermentioning
confidence: 99%
“…P-cadherin upregulation was frequently observed in various malignant tumours, including breast, gastric, endometrial, colorectal and pancreatic carcinomas, and is correlated with poor survival of breast cancer patients (Hardy et al, 2002, Imai et al, 2008, Stefansson et al, 2004, Taniuchi et al, 2005. In contrast, significantly low levels of the P-cadherin gene expression were detected in a diverse panel of normal tissues (Imai et al, 2008). Thus, disruption of P-cadherin signalling represents an intriguing opportunity for the development of novel targeted therapeutic agents in cancer.…”
mentioning
confidence: 99%
“…The upregulation of P-cadherin was frequently observed in various malignant tumors, including breast, colon, lung, and pancreatic tumors, and correlated with poor survival of breast cancer patients (15,20,21). In contrast, significantly low levels of the P-cadherin gene expression were detected in a diverse panel of normal tissues (22). Thus, disruption of P-cadherin signaling represents an intriguing opportunity for the development of novel targeted therapeutic agents.…”
mentioning
confidence: 99%